The microbiota of hematophagous ectoparasites collected from migratory birds. - Francesco Cerutti (PLoS ONE, 2018)
Arthropod vectors are responsible for the transmission of human pathogens worldwide. Several arthropod species are bird ectoparasites, however, no study to date has characterized their microbiota as a whole. We sampled hematophagous ectoparasites that feed on migratory birds and performed 16S rRNA gene metabarcoding to characterize their microbial community. A total of 194 ectoparasites were collected from 115 avian hosts and classified into three groups: a) Hippoboscidae diptera; b) ticks; c) other arthropods. Metabarcoding showed that endosymbionts were the most abundant genera of the microbial community, including Wolbachia for Hippoboscidae diptera, Candidatus Midichloria for ticks, Wolbachia and Arsenophonus for the other arthropod group. Genera including pathogenic species were: Rickettsia, Borrelia, Coxiella, Francisella, Bartonella, Anaplasma. Co-infection with Borrelia-Rickettsia and Anaplasma-Rickettsia was also observed. A global overview of the microbiota of ectoparasites sampled from migratory birds was obtained with the use of 16S rRNA gene metabarcoding. A novel finding is the first identification of Rickettsia in the common swift louse fly, Crataerina pallida. Given their possible interaction with pathogenic viruses and bacteria, the presence of endosymbionts in arthropods merits attention. Finally, molecular characterization of genera, including both pathogenic and symbiont species, plays a pivotal role in the design of targeted molecular diagnostics.